Imiquimod nanocrystal-loaded dissolving microneedles prepared by DLP printing - Petrová, Eliška; Chvíla, Stanislav; Štěpánek, František; Zbytovská, Jarmila; Lamprou, Dimitrios A (Drug delivery and translational research, 2025)
The utilization of 3D printing- digital light processing (DLP) technique, for the direct fabrication of microneedles encounters the problem of drug solubility in printing resin, especially if it is predominantly composed of water. The possible solution how to ensure ideal belonging of drug and water-based printing resin is its pre-formulation in nanosuspension such as nanocrystals. This study investigates the feasibility of this approach on a resin containing nanocrystals of imiquimod (IMQ), an active used in (pre)cancerous skin conditions, well known for its problematic solubility and bioavailability. The resin blend of polyethylene glycol diacrylate and N-vinylpyrrolidone, and lithium phenyl-2,4,6-trimethylbenzoylphosphinate as a photoinitiator, was used, mixed with IMQ nanocrystals in water. The final microneedle-patches had 36 cylindrical microneedles arranged in a square grid, measuring approximately 600 μm in height and 500 μm in diameter. They contained 5wt% IMQ, which is equivalent to a commercially available cream. The homogeneity of IMQ distribution in the matrix was higher for nanocrystals compared to usual crystalline form. The release of IMQ from the patches was determined ex vivo in natural skin and revealed a 48% increase in efficacy for nanocrystal formulations compared to the crystalline form of IMQ.
Keywords: Dermal delivery; polyethylenglykoly; Needles; mikroinjekce; aplikace kožní; Nanoparticles; jehly; nanočástice; kůže; Imiquimod; rozpustnost; Polyethylene Glycols; Drug Delivery Systems; Microinjections; Animals; imichimod; Skin; zvířata; Povidone; Drug Liberation; kožní absorpce; Skin Absorption; Microneedles; povidon; Nanocrystals; uvolňování léčiv; 3D tisk; Printing, Three-Dimensional; lékové transportní systémy; Solubility; 3D printing; Administration, Cutaneous